Self-assembly of s-indacene-tetrone on Cu(111): molecular trapping and patterning of Cu adatoms. Issue 15 (30th March 2023) - Kalashnyk, Nataliya; Denawi, Adam Hassan; Dumur, Frédéric; Gigmes, Didier; Bouju, Xavier; Clair, Sylvain
Abstract : The supramolecular self-assembly of indacene-tetrone on the Cu(111) surface exhibits a variety of well-ordered phases stabilized by different bonding types depending on the annealing temperature. Abstract : The supramolecular self-assembly of s -indacene-1, 3, 5, 7(2 H, 6 H )-tetrone on the Cu(111) surface was investigated under ultrahigh vacuum by room-temperature scanning tunneling microscopy supported by theoretical modelling based on density functional theory. In total, six different phases were found, driven by hydrogen bonding, metal ligand coordination or covalent coupling. Host–guest interactions allowed for the accommodation of molecular or metal clusters inside the open nanoporous patterns. In one phase, molecular trapping was stochastically observed inside the large periodic nanopores created inside the supramolecular network. The three metal–organic networks observed resulted in the creation of different kinds of regular arrays of isolated metal adatoms or adatom clusters with a lattice period larger than 1 nm.